1990
DOI: 10.1177/000348949009901104
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of the Scala Tympani in the Human and Cat with Reference to Cochlear Implants

Abstract: The width, height, and cross-sectional area of the scala tympani in both the human and cat were measured to provide dimensional information relevant to the design of scala tympani electrode arrays. Both the height and width of the human scala tympani decreased rapidly within the first 1.5 mm from the round window. Thereafter, they exhibit a gradual reduction in their dimension with increasing distance from the round window. The cross-sectional area of the human scala tympani reflects the changes observed in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 11 publications
3
47
0
Order By: Relevance
“…Computational modeling approaches may prove particularly useful in addressing longstanding issues of across-species differences in cochlear or nerve-fiber anatomy (Hatsushika et al 1990;Nadol et al 1990;Felix 2002) that could render some of our results inapplicable to the physiology of electrically stimulated human ANFs. For example, while feline and human cochleae are similar, they vary in gross dimensions and shape of the first turn.…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling approaches may prove particularly useful in addressing longstanding issues of across-species differences in cochlear or nerve-fiber anatomy (Hatsushika et al 1990;Nadol et al 1990;Felix 2002) that could render some of our results inapplicable to the physiology of electrically stimulated human ANFs. For example, while feline and human cochleae are similar, they vary in gross dimensions and shape of the first turn.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2). 1 The cochlea model is constructed according to our early work, 7 and is adapted to the dimension of scala tympani based on the study of Hatsuchika et al 12 The modeled cochlea is embedded in a bone, which is not shown in the figure, to form the complete model. Although the structure of a real cochlea is spiral and tapering, the basal turn, especially for the first half turn, is close to a circular shape with a similar dimension.…”
Section: Model Of the Human Cochlea And Analysis Approachmentioning
confidence: 99%
“…Methods using several type of plastic casts have been widely employed to evaluate the dimensions of cochlear anatomy (Zrunek et al, 1980;Zrunek and Lischka, 1981;Dimopoulos and Muren, 1990;Hatsushika et al, 1990;Wysocki, 1999;Erixon et al, 2009;RaskAndersen et al, 2011), but they do not allow accurate preservation of the geometric relationships of fragile cochlear structures and artifact-free measurements. Microdissections enable measurements of basic external dimensions of the cochlea like the width of the cochlear base (Wright and Roland, 2005), but as plastic casts, it cannot provide detailed three-dimensional reconstruction.…”
Section: Introductionmentioning
confidence: 99%